Pedagogies of Resistance: Reclaiming Student Autonomy through Student-Led Teaching in Higher Education - Lehner, Daniela; Weber, Björn (Critical Education, 2026)
This article explores student-led teaching as a counter-hegemonic educational practice in response to the neoliberal restructuring of higher education. Drawing on critical pedagogy, we reflect on the co-development and facilitation of a student-led course at a university in Austria. Guided by a practice-based approach informed by reflexive thematic analysis, we used our field notes to reveal the many ways in which students co-created and shaped the course. The findings indicate that student-led teaching can foster meaningful engagement, a sense of ownership, and the development of critical political agency. At the same time, uneven participation revealed challenges, with more confident or experienced students at times dominating discussions. These dynamics underscore the need for attentiveness to power relations and inclusive facilitation. The most transformative moments emerged when classroom discussions connected with lived experience, especially when they involved collective social engagement beyond the university walls, affirming the value of linking higher education to collective action.